Perbedaan Individu dan Perkembangan Kognitif Anak Serta Implikasinya Terhadap Pembelajaran - Arifmiboy Arifmiboy (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2014)
Every student is an individual as a unique person that has different intelligence, talent, learning style, personality, and temperament. It is important for teachers to recognize and understand individual differences of their fellows so that they can select the best way to carry out the learning activity well. There are five items of individual differences discussed in this paper, namely: (1)intelligence; (2)talent (3)learning style (4)personality and (5) temperament. Furthermore, each student commits different steps ofcognitive development for his own. Due to these phenomena, teachers need to consider and arrange learning strategy which is suitablewith students’ characteristics and cognitive development.